Bilateral proximal deep vein thrombosis and COVID‐19 in a patient with absence of inferior vena cava: A case report and review of literature - Yaser Jenab; Parham Ghafouri; Kaveh Hosseini; Shapour Shirani; Mahmood Shirzad (Clinical Case Reports, 2022)
Abstract Bilateral proximal deep vein thrombosis (DVT) in the lower extremities of young patients should raise suspicion over pro‐thrombotic conditions and venous anatomical abnormalities, even in the presence of other precipitating factors, such as viral infection. The authors present a 33‐year‐old man with bilateral DVT and absence of inferior vena cava (AIVC), who also had concurrent COVID‐19, and discuss the management of this patient.